Blockchain+big data: Smart contract design for decentralized financial sharing platform - Zhou, Xiaohua (Edelweiss Applied Science and Technology, 2025)
This article takes Company A as an example to focus on the optimization path of a decentralized financial sharing platform that integrates blockchain technology and big data. By analyzing the hierarchical architecture and core technologies of blockchain and combining them with the capabilities of big data in data integration, analysis, and risk prediction, the author proposes a smart contract design scheme for a financial sharing platform based on "blockchain + big data." The author studied and designed a solution including architecture reconstruction, security optimization, and process automation to address the centralized data security risks, information asymmetry, business process redundancy, and talent shortage issues of Company A’s existing platform. Empirical results indicate that this solution effectively addresses the pain points of data silos, high trust costs, and inefficient processes in traditional financial sharing platforms, providing a balanced, secure, and intelligent technological path for the digital transformation of large enterprise finance. The blockchain technology itself has unique advantages: decentralization, trustlessness, and a unique distributed ledger form. These advantages can be used to optimize the architecture of financial sharing platforms, promote and apply them, thereby improving financial work efficiency and expanding enterprise economic benefits.